Clinical needs assessment to inform development of a new assay to detect antimalarial drugs in patient samples: A case study. - Erin S Coonahan; Chanaki Amaratunga; Carole A Long; Joel Tarning (Public Library of Science (PLoS), 2023)
Point-of-care assays have greatly increased access to diagnostic information and improved healthcare outcomes globally, especially in the case of tropical diseases in rural settings. Increased recognition of the impact of these tools and increased funding, along with advances in technology have led to a surge in development of new assays. However, many new tools fail to fulfill their intended purpose due to a lack of clinical impact, operational feasibility, and input from envisioned operators. To be successful, they must fit into existing clinical decision-making models and be designed in collaboration with end users. We describe a case study of the development of a new low-cost sensor for antimalarial drugs, from initial planning through collection and incorporation of design feedback to final assay design. The assay uses an aptamer-based sensor to detect antimalarial drugs from patient samples for tracking antimalarial use in Southeast Asia, a region with a long history of emerging antimalarial drug resistance. Design and use-case input was collected from malaria control experts, researchers, and healthcare workers to develop target product profiles. Data was collected via surveys and in-person interviews during assay development and ultimately informed a change in assay format. This aptamer sensor platform can be easily adapted to detect other small molecule and protein targets and the design process described here can serve as a model for the development of effective new assays to improve access to healthcare technology.